DETERMINATION OF SCOUR DEPTHS AROUND SIDE-WEIR ON AN ALLUVIAL RIVERS - Onen, Fevzi; Agaccioglu, Hayrullah (YILDIZ TECHNICAL UNIV, 2006)
An experimental investigation of the local depth of scour around side-weirs located on an alluvial river is presented in this paper. The reduction in velocities and shear stresses causes to the development of the stagnation and reverse flow at the downstream end of the side-weir in the main channel. The changes in shear stress are found to be responsible a scour hole forms between the longitudinal bar adjacent to main channel and outer bank at the downstream end of the side-weir. The depth of clear-water scour approaches asymptotically to equilibrium with time depending on the flow intensity. It is also found that the equilibrium depth of scour depends on the dimensionless parameters of flow intensity, flow shallowness, weir crest height and side-weir length. Although when the flow intensity is less than 0.45 there is no scour, scour equilibrium depth increases almost linearly with the ratio of flow intensity and the maximum value of scour occurs at depth when the flow intensity is equal to 1.0. Flow intensity also increases when other dimensionless parameters increase.
Keywords: Alluvial bed; clear-water scour; secondary circulation; side-weir and threshold velocity; Engineering